Relationship Between Balance and Attentional Function in Deaf and Healthy People - Aida Asariha; Elaheh Azadian (Islamic Azad University, Hamedan Branch, 2018)
Objective: Deafness, not only negatively affect communication, but also is associated with other physical disorders such as impaired balance and cognitive function. The evaluation of balance and cognitive function in deaf people has been considered in a few studies, but less studies have investigated the relationship between these two factors. Hence, the purpose of this study was to examine the relationship between cognitive function and balance performance in deaf and normal-hearing subjects. Methods: Participants were 39 deaf students and 40 normal hearing students (controls) recruited from exceptional schools in Hamedan, Iran. Their cognitive function was measured by Flanker task, continuous performance test and Stroop Task. Their balance was measured by the Bruininks Oseretsky Test of Motor Proficiency. Collected data were analyzed in SPSS software using Mann-Whitney U and Wilcoxon tests considering the significance level of P<0.05. Results: Deaf subjects had significantly poorer balance and cognitive function than controls. The highest correlation was observed between their performance under Flanker task and heel-to-toe walking (P<0.05).  Conclusion: Deaf people are more dependent on visual information to perform balance exercises. Increased attentional capacity may also improve motor function in these individuals.